Metode Pemulusan Eksponensial Tripel TipeBrown pada Peramalan Jumlah Produksi Jagung Kabupaten Lima Puluh Kota - Tina Islamiati; Suherman Suherman (Journal of Mathematics UNP, 2020)
Abstract—Corn is the main staple food after rice which is a buffer for national food security. Apart from that it is also the main raw material for the animal feed industry  in Lima Puluh Kota. More than 55% of corn production is used as animal feed ingredients. The purpose of this study was to establish a forecasting model for the amount of corn production in Lima Puluh Kota using the Brown’s exponential smoothing method and predict the amount of corn production based on the model that was formed. This type of research is applied research and the data used are secondary data obtained from the official website of the Central Statistics Agency of Lima Puluh Kota. Forecasting method used is the Brown Type Triple Exponential Smoothing Method. From the forecasting model the forecast results are obtained in years 2018 and 2019 that is 31.751,598 ton dan 39.509,526 ton. Keywords—Corn Production Amount, Forecasting,  Smoothing Exponential.